Improving students' digital literacy through an AR-assisted e-module on fruit and seed morphology using the RICOSRE model - Mardian, Anggraini; Mahanal, Susriyati; Sulisetijono, Sulisetijono (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
A preliminary study showed that students' digital literacy was still at a relatively sufficient level. Digital literacy, a key 21st-century skill, is essential for Biology Education students to thrive in the digital era. This research aims to determine the effect of the e-module morphological structure of fruits and seeds based on RICOSRE assisted by AR on students' digital literacy. This study employs a quantitative approach, utilizing a quasi-experimental design with a non-randomized control-group pretest-posttest design. The research subjects were third-semester students of the S1 Biology Education program at Malang State University, with a total of 57 students divided into two classes, 31 students in the experimental class and 26 students in the control class. Data were collected using three instruments: a 20-item multiple-choice test for the cognitive dimension, a 20-item Likert-scale questionnaire for the social-emotional dimension, and an observation sheet with 5 indicators for the technical dimension, and all these instruments have been validated. The data types included test scores, questionnaire responses, and observation results. Data analysis included normality and homogeneity tests, followed by One-Way ANCOVA. The results of research showed that the use of the AR-assisted RICOSRE-based e-module had a significant effect on students’ digital literacy across all dimensions (sig. < 0.05). Future researchers may also explore the integration of AR and structured learning models like RICOSRE in other subjects to enhance various 21st-century skills.